The Moderating Effect of Audit Opinion on The Local Government Financial Performances and The Disclosure Compliance of Financial Information - Jamal Akrom; Amrie Firmansyah (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
This study is aimed to analyze the effect of financial performance indicators such as absorption of local expenditure ratio, effectiveness ratio, and financial independence ratio on the disclosure compliance of financial information on the website, as well as audit opinion as moderating variable. The sample of the study is the local governments in Java with consisting of 81 selected local governments within three years period. The data are analyzed with multiple regression analysis using the fixed-effect method.The results show that the absorption of the local budget ratio cannot encourage the disclosure compliance of financial information on the website. While the effectiveness ratio and the financial independence ratio are positively associated with the disclosure compliance of financial information on the website. This study also finds that audit opinion weakens the effect of financial independence ratio on the disclosure compliance of financial information on the website. However, audit opinion cannot moderate the effect of absorption of local budget ratio and the effectiveness ratio on the disclosure compliance of financial information on the website. Keywords: audit opinion; financial performances, information